Local Increase of Arginase Activity in Lesions of Patients with Cutaneous Leishmaniasis in Ethiopia - Abebe, Tamrat (Public Library of Science, 2012)
BACKGROUND: Cutaneous leishmaniasis is a vector-borne disease that is in Ethiopia mainly caused by the parasite Leishmania aethiopica. This neglected tropical disease is common in rural areas and causes serious morbidity. Persistent nonhealing cutaneous leishmaniasis has been associated with poor T cell mediated responses; however, the underlying mechanisms are not well understood. METHODOLOGY/PRINCIPAL FINDINGS: We have recently shown in an experimental model of cutaneous leishmaniasis that arginase-induced L-arginine metabolism suppresses antigen-specific T cell responses at the site of pathology, but not in the periphery. To test whether these results translate to human disease, we recruited patients presenting with localized lesions of cutaneous leishmaniasis and assessed the levels of arginase activity in cells isolated from peripheral blood and from skin biopsies. Arginase activity was similar in peripheral blood mononuclear cells (PBMCs) from patients and healthy controls. In sharp contrast, arginase activity was significantly increased in lesion biopsies of patients with localized cutaneous leishmaniasis as compared with controls. Furthermore, we found that the expression levels of CD3ζ, CD4 and CD8 molecules were considerably lower at the site of pathology as compared to those observed in paired PBMCs. CONCLUSION: Our results suggest that increased arginase in lesions of patients with cutaneous leishmaniasis might play a role in the pathogenesis of the disease by impairing T cell effector functions.